1992
DOI: 10.1590/s0102-33061992000200001
|View full text |Cite
|
Sign up to set email alerts
|

Produção primária líquida em área queimada e não queimada de campo sujo de cerrado (Planaltina - DF)

Abstract: RESUMO -Foi estimada a produção primária líquida aérea de duas áreas de campo sujo de cerrado em Planaltina (DF), sendo uma preservada e outra queimada no início do experimento. A produção foi estimada através das diferenças entre o peso seco da fitomassa herbácea aérea coletada quinzenalmente. O estudo foi realizado de outubro de 1980 a abril de 1981, que corresponde ao período das chuvas no DF. A produção primária líquida aérea do estrato herbáceo da área queimada (176 :!: 33 g m-2 ) foi maior que a observad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
3

Year Published

2001
2001
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 13 publications
1
4
0
3
Order By: Relevance
“…This result is consistent with the fact that grass ground cover shows a high increase immediately after fire (Meirelles and Henriques 1992). Over time, this cover decreases and shrub and tree cover increases after fire (Moreira 2000).…”
Section: Small Mammal Successionsupporting
confidence: 84%
See 1 more Smart Citation
“…This result is consistent with the fact that grass ground cover shows a high increase immediately after fire (Meirelles and Henriques 1992). Over time, this cover decreases and shrub and tree cover increases after fire (Moreira 2000).…”
Section: Small Mammal Successionsupporting
confidence: 84%
“…The pattern of species replacement over time depends critically on how quickly the habitat gradient trajectory changes. Previous studies showed that initially after fire, the rate of increase in herbaceous cover is higher than for woody cover (Meirelles and Henriques 1992). In our model we assumed that the rate of change is higher in the initial stages of succession and decreases with time ( Figure 3B).…”
Section: The Modelmentioning
confidence: 95%
“…The dead standing herbaceous layer is a usually underestimated component of litter. In typical cerrado areas the dead standing herbaceous achieved 4.7 Mg ha -1 (Meirelles and Henriques, 1992). The reduction by 22% in the fine litter production one year after fire (Nardoto et al, 2006) can be related to the higher mortality rates of woody species after successive fire events (Sato and Miranda, 1996;Sato et al, 1998).…”
Section: Impacts Of Disturbances and Management On Carbon Stocks And mentioning
confidence: 99%
“…ANCOVA ( primary production [21], as well as the mortality of the aboveground parts of the majority of the herb layer are accompanied by a decrease in the belowground biomass present in the upper soil layers which are submitted to a severe drought [31].…”
Section: Correlation (R)mentioning
confidence: 99%